An evaluation of photographic activity schedules to increase independent playground skills in young children with autism. Issue 4 (10th June 2016) - Akers, Jessica S.; Higbee, Thomas S.; Pollard, Joy S.; Pellegrino, Azure J.; Gerencser, Kristina R.
Abstract : We used photographic activity schedules to increase the number of play activities completed by children with autism during unstructured time on the playground. All 3 participants engaged in more playground activities during and after training, and they continued to complete activities when novel photographs were introduced.